Design and Immunological Evaluation of a Hybrid Peptide as a Potent TLR2 Agonist by Structure-Based Virtual Screening - Zhang, Lulu; Wei, Xubiao; Zhang, Rijun; Mozdziak, Paul E.; Si, Dayong; Ahmad, Baseer; Cheng, Qiang; Tong, Yucui (Frontiers in Cell and Developmental Biology, 2021)
Immunity is a versatile defensive response that is involved in protecting against disease by identifying and destroying self and nonself harmful substances or microbiological toxins. As a state of temporary or permanent immune dysfunction, immunosuppression can make an organism more susceptible to infection, organ injury, and cancer due to damage to the immune system. It has taken a long time to develop new immunomodulatory agents to prevent and treat immunosuppressive diseases, but with slow progress. In recent years, Toll-like receptor 2 (TLR2) agonists have been reported to have profound effects on the immune system and are thereby regarded as potent immunomodulatory candidates. TP5 and LL-37, the potent immunomodulatory agents, have been reported to produce a robust innate immune response by binding to TLR2. However, their development has been weakened by several concerns, such as potential cytotoxicity, weak physiological stability and poor immunomodulatory activity. To overcome these challenges, hybridization has been proposed. Therefore, six hybrid peptides (LTPa, LTPb, LTPc, TPLa, TPLb, and TPLc) were designed by combining the full-length TP5 with a characteristic fragment of LL-37 that included LL-37 (13-36), LL-37 (17-29), and LL-37 (13-31). LTPa, the most potent TLR2 agonist, was simply and effectively screened by molecular docking and in vitro experiments. Furthermore, the immunomodulatory effects of LTPa were confirmed by a CTX-immunosuppressed murine model, which showed that LTPa successfully inhibited immunosuppression, increased immune organ indices, enhanced DC maturation, regulated T lymphocyte subsets, and increased cytokine and Ig contents. Our study also revealed that the immunomodulatory effects of LTPa are associated with binding to TLR2, forming TLR2 clusters, and activating the NF-кB signaling pathway.